Reproductive, clinical and biological markers of perimenopause - О. О. Єфіменко; І. М. Ретунськ; О. С. Зеленько (Publishing House TRILIST, 2018)
The problems of aging women both in the world and in our country are becoming increasingly relevant. The sharp increase in the incidence among women of the age category, which coincides with the age of menopause, is a serious argument for considering this period and the associated changes as one of the priorities of modern medicine. Already today, despite the general tendency to aging of the population, a third of the life of the majority of women falls on the post-menopausal period, which acquires a special social and even state significance. However, these changes begin at a younger age, which requires close attention of specialists, because it is at this stage that the development of long-term programs to preserve both the reproductive and the general health of the female population is important. The article considers modern views on the problem of ovarian function diminishing in perimenopause and the problem of aging in general. Reproductive and biological age markers and hormonal disorders causing clinical manifestations of perimenopause are given. Attention is paid to the definition of psychological age, its influence on the psychological status of a woman whose passport age is over 40 years old, which coincides with the peak of her professional and social activities. Analyzed modern views on improving the quality of life of women who are in the perimenopausal period. Currently, there are many methods for timely assessment of disorders in systems and organs that can provoke the occurrence of age-related diseases. Therefore, the task of modern medicine is to prevent early aging and introduce preventive methods that improve the quality of life and increase its duration. As the authors of the article note, the assessment of biological and reproductive age is important for the prevention of diseases that can be avoided by following simple guidelines for optimizing lifestyle.